2012
DOI: 10.1086/663827
|View full text |Cite
|
Sign up to set email alerts
|

The Small-Area Hypothesis: Effects of Progress Monitoring on Goal Adherence

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. This article examines a small-area hypothesis: individuals striving toward a goal end state exhibit greater motivation when their attention is directed to whichever is smaller … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
112
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 124 publications
(124 citation statements)
references
References 37 publications
11
112
1
Order By: Relevance
“…In this case, the first action accomplishes 100% of the progress to date, whereas the second action accomplishes only 50% of the progress to date (Bonezzi, Brendl, & De Angelis, 2011). In one study, Koo and Fishbach (2012) provided participants with a frequent-buyer card ("buy 10 get 1 free") that manipulated goal progress and focus on the beginning versus end stage of goal pursuit. Cards drawing participants' attention to the beginning stages featured three stamps for the low progress condition and seven stamps for high progress.…”
Section: The Outcome: What Will I Accomplish?mentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the first action accomplishes 100% of the progress to date, whereas the second action accomplishes only 50% of the progress to date (Bonezzi, Brendl, & De Angelis, 2011). In one study, Koo and Fishbach (2012) provided participants with a frequent-buyer card ("buy 10 get 1 free") that manipulated goal progress and focus on the beginning versus end stage of goal pursuit. Cards drawing participants' attention to the beginning stages featured three stamps for the low progress condition and seven stamps for high progress.…”
Section: The Outcome: What Will I Accomplish?mentioning
confidence: 99%
“…For example, people who naturally enjoy typing emails would be more motivated to respond to their 376 emails than those who intrinsically dislike this activity-even if both groups recognize the external benefits of being responsive. Education researchers have long linked improved academic performance to greater intrinsic motivation F I G U R E 2 Motivation as a function of level of progress and focus on accumulated versus remaining purchases to receive a reward (Koo & Fishbach, 2012) Focus: Accumulating 7 (Deci, Vallerand, Pelletier, & Ryan, 1991;Lepper, Corpus, & Iyengar, 2005;Pintrich & De Groot, 1990). In other goal domains, Woolley and Fishbach (2017) found that the extent to which people enjoyed pursuing a goal was a better predictor of their persistence at following through with their New Year's resolutions, and their goals to study and exercise, than was the extent to which people felt these goals were important for them.…”
Section: The Process: How Will I Experience the Goal?mentioning
confidence: 99%
“…The psychophysics explanation underlying the goal gradient effect makes another prediction as well: the ''small area hypothesis'' (Koo & Fishbach, 2012). This hypothesis suggests that for goals with a clear end state, individuals will exhibit greater motivation when they focus on their completed progress at the beginning and their lack of progress toward the end.…”
Section: The Course Of Goal Pursuitmentioning
confidence: 99%
“…Up to the midpoint (50%) of a goal, attention to completed actions increases motivation more than attention to remaining actions. Beyond the midpoint, this pattern reverses such that attention to remaining actions increases motivation more than attention to completed actions (Bonezzi, Brendl, & Angelis, 2011;Koo & Fishbach, 2012).…”
Section: The Course Of Goal Pursuitmentioning
confidence: 99%
See 1 more Smart Citation